Neuron-specific enolase as a prognostic biomarker in acute ischemic stroke patients treated with reperfusion therapies - Freitas, Tiago Esteves; Costa, Ana Isabel; Neves, Leonor; Barros, Carolina; Martins, Mariana; Freitas, Pedro; Noronha, Duarte; Freitas, Patrício; Faria, Teresa; Borges, Sofia; Freitas, Sónia; Henriques, Eva; et al. (Frontiers in Neurology, 2024)
Introduction: Ischemic stroke is a significant global health concern, with reperfusion therapies playing a vital role in patient management.Neuron-specific enolase (NSE) has been suggested as a potential biomarker for assessing stroke severity and prognosis, however, the role of NSE in predicting long-term outcomes in patients undergoing reperfusion therapies is still scarce.To investigate the association between serum NSE levels at admission and 48 hours after reperfusion therapies, and functional outcomes at 90 days in ischemic stroke patients.Methods: This study conducted a prospective cross-sectional analysis on consecutive acute ischemic stroke patients undergoing intravenous fibrinolysis and/or endovascular thrombectomy. Functional outcomes were assessed using the modified Rankin Scale (mRS) at 90 days post-stroke and two groups were defined according to having unfavorable (mRS3-6) or favorable (mRS0-2) outcome. Demographic, clinical, radiological, and laboratory data were collected, including NSE levels at admission and 48h.Spearman´s coefficient evaluated the correlation between analyzed variables. Logistic regression analysis was performed to verify which variables were independently associated with unfavorable outcome. Two ROC curves determined the cut-off points for NSE at admission and 48h, being compared by Delong test.Results: Analysis of 79 patients undergoing reperfusion treatment following acute stroke revealed that patients with mRS 3-6 had higher NIHSS at admission (p<0.0001), higher NIHSS at 24h (p<0.0001), and higher NSE levels at 48h (p=0.008) when compared to those with mRS 0-2.Optimal cut-off values for NSE0 (>14.2 ng/mL) and NSE48h (>26.3 ng/mL) were identified, showing associations with worse clinical outcomes. Adjusted analyses demonstrated that patients with NSE48h >26.3 ng/ml had a 13.5 times higher risk of unfavorable outcome, while each unit increase in NIHSS24h score was associated with a 22% increase in unfavorable outcome. Receiver operating characteristic analysis indicated similar predictive abilities of NSE levels at admission and 48 hours (p=0.298).Additionally, a strong positive correlation was observed between NSE48h levels and mRS at 90 days (r=0.400 and p<0.0001), suggesting that higher NSE levels indicate worse neurological disability post-stroke. Conclusion: Serum NSE levels at 48 hours post-reperfusion therapies are associated with functional outcomes in ischemic stroke patients, serving as potential tool for patient longterm prognosis.